Heat Transfer Enhancement With Nanofluids – A Review - Adnan Mohammed, Hussein; K. V., Sharma; R. A., Bakar; K., Kadirgama (Faculty Mechanical Engineering, UMP, 2013)
This paper presents a review of the studies undertaken on convection heat transfer with nanofluids. Initial studies were directed towards the determination of the properties of nanofluids, especially their thermal conductivity and viscosity. The studies indicate that thermal conductivity and viscosity increase with an increase in the concentration of the nanofluid. Experiments were conducted with different nanofluids, at various concentrations and temperature ranges, for the estimation of the heat transfer coefficient and friction factor for water-based nanofluids. All the studies confirmed enhancement of the heat transfer coefficient with an increase in concentration. The experimental ranges of temperature undertaken by the authors were different for different nanofluids. Certain studies with smaller particle sizes indicated an increase in heat transfer enhancements when compared with values obtained when using larger particle sizes. It is observed that the concentration of the nanofluid, the operating temperature, the particle size and shape, together with the material of the nanoparticle dispersed in the base liquid, have significant influence on the heat transfer coefficient. All the studies indicate a nominal increase in pressure drop.